PTU-052 Long Term outcome of Patients with Reflux Symptoms and Symptomatic Esophageal Dysfunction during and after a Standardized Test Meal:a High-Resolution Manometry Study. (4th June 2013) - Sweis, R; Brady, G; Anggiansah, A; Lee, A; Valdes, A; Wong, T; Fox, M
Abstract : Introduction: Recently we presented novel methodology for the assessment of oesophageal function and symptoms during and after a standard test meal. 1 In the absence of a "gold standard", outcome data provides insight into the clinical impact of this test in patients with reflux symptoms Methods: 18 patients referred for investigation of reflux symptoms and 10 healthy volunteers underwent High Resolution Manometry (HRM) with 5ml water, 200ml water drink and test meal followed by 10min post-prandial observation. 24hr pH studies were performed in patients. The number of Symptoms Associated with oesophageal Dysfunction(SAD) was calculated. HRM findings and initial diagnosis were compared with the final diagnosis and outcome at 2 years Results: No symptoms occurred with 5ml water. 12/18(67%) patients had SAD (mean SAD 2(range 0–7)) during/after the meal. Compared to 5ml water, manometric diagnosis was altered in 12/18(67%). No healthy volunteers had SAD. 11/18 patients had GORD on pH studies. By 2 years, 5/11 had anti-reflux surgery with excellent outcome. All 5 exhibited dysmotility (e.g. hypotensive/failed peristalsis) during the meal with symptomatic postprandial reflux events (transient lower oesophageal sphincter relaxation + common cavity). Of the 6/11 with GORD who did not have surgery, 2 declined it despite pathological pH results and symptomatic reflux events after the meal; both remain symptomatic despite acid-reducing therapy. The remaining 4 of 6 patients also had symptomatic dysmotility but were not offered surgery. 2 with severe hypotensive dysmotility and symptomatic reflux responded to acid suppression. 1 with (peptic) outlet obstruction and 1 with diffuse spasm did not respond to medication. Of the 7 with functional heartburn (negative pH results), 2 who had normal HRM responded to dietary/stress management. 2 with symptomatic reflux during HRM had good response to acid-suppression (i.e. false neg pH study). The final 3 with reflux-like symptoms had outflow obstruction identified only during the meal; 1 had good outcome after dilatation, 1 was too frail for therapy and remains symptomatic and the last was lost to follow-up. Conclusion: HRM studies which include a test meal and post-prandial observation provide an objective explanation for symptoms in the majority of patients referred for investigation of "reflux" symptoms. Long-term follow-up suggests this information can guide management especially in patientswithout definitive diagnosis following standard 5 ml water HRM and negative pH-studies Disclosure of Interest: None Declared Reference: Sweis R et al. Gastro 2011; 140